Analysis of Novel Assistive Robotic Multi‐Stage Underwater Lift Design for Swimmer Safety. Issue 7 (20th April 2022) - Laxman, Pillalamarri; Jain, Anuj
Abstract: Unintentional deaths particularly near swimming pools are alarmingly increasing in recent times. The rate of increase in deaths was reported in the world health organization and other national health magazines. There were very few inventions and research work done on autonomous rescue designs. The paper introduced new methods and techniques to address the issues. The paper introduces very novel architecture; novel multilayer approaches especially worked on fail‐proof autonomous rescue techniques by using natural buoyancy as a main source of mechanical power in lifting drowning persons from the water. The trials conducted by the paper were accurate and reliable and the proposed autonomous drown‐rescue system design is suitable for most the situations. The placement of sensors, elevator, semiautomatic arrangements such as panic switches, and buoyancy helped elevator are the total innovative approaches in addressing the situation (cause). There is no big limitation in the proposed methods except 20–30% of the total cost of the construction of the swimming pool which is not a problem when addressing alarmingly increasing deaths due to drowning in all age groups people. The methods discussed in the paper are all possible and feasible cost‐effective methods and add more confidence in maintaining a pool in‐house without any health risks. The governments and communities must frame rules to implement the proposed system as mandatory to maintain a pool that is 100% safe for all age groups. The methods addressed in the paper are completely novel and new. The paper contributes major design contributions for the detection of drowning accidents using underwater and buoyancy‐dependent lifts, proximity sensors, and laser tripwires.